I wish that I had duck feet - Seuss, Dr.; Tobey, B. (Barney), 1906-1989 (New York : Harper Collins Children's Books, 1993)
A boy imagines what it would be like if he had such things as duck feet, a whale spout, and an elephant's trunk.
Keywords: Stories in rhyme; Imagination -- Fiction